Testing the Random Utility Hypothesis Directly. Issue 625 (19th July 2019) - McCausland, William J; Davis-Stober, Clintin; Marley, AAJ; Park, Sanghyuk; Brown, Nicholas
Abstract: We test a set of inequalities in choice probabilities, shown to be necessary and sufficient for random utility by Falmagne (1978 ). We run an experiment in which each of 141 participants chooses six times from each doubleton or larger subset of a universe of five lotteries. We compute Bayes factors in favour of random utility, versus an alternative with unrestricted choice probabilities. There is strong evidence that a large majority of participants satisfy random utility; however, there is strong evidence against random utility for four participants. Results are fairly robust to the choice of prior.